Articular and Meniscal Pathology Associated with Primary Anterior Cruciate Ligament Reconstruction - Ghodadra, Neil; Mall, Nathan A.; Karas, Vasili; Grumet, Robert C.; Kirk, Spencer; McNickle, Allison G.; Garrido, Cecilia Pascual; Cole, Brian J.; Bach, Bernard R., Jr (The Journal of Knee Surgery, 2013)
Background The abnormal kinematics, contact pressures, and repeated episodes of instability observed in chronic anterior cruciate ligament (ACL) deficiency suggest that these patients may be predisposed to early degenerative changes and associated pathologies such as meniscal tears and chondral injury. Injury to the cartilage and associated structures at the time of ACL rupture, in combination with the inflammatory mediators released at the time of injury, may create irreversible damage to the knee despite restoration of normal knee kinematics with an ACL reconstruction.Hypothesis Patients undergoing acute ACL reconstruction have a higher incidence of lateral meniscal tears and less severe chondral changes when compared with patients undergoing late ACL reconstruction. Older patients likely have a higher incidence of chondral and meniscal pathology compared with younger patients.Methods A retrospective chart review of a single surgeon's ACL practice over 20 years was performed. A surgical data packet was used to record patient demographics, location, grade, and number of chondral injuries as well as location and pattern of meniscal injuries at the time of ACL reconstruction. Patients (N = 709) were divided into three subgroups according to their time from injury to surgery; acute (less than 4 weeks, N = 121), subacute (4 to 8 weeks, N = 146), and chronic (8 weeks or more, N = 442).Results Older patients had a higher incidence of more severe chondral grade and number of chondral injuries at the time of ACL reconstruction. Patients undergoing surgery more than 8 weeks after injury had a statistically significant more severe chondral grade in the medial compartment when compared with those that had surgery less than 8 weeks after injury. A similar observation was not found in the lateral compartment. With regard to meniscal pathology, full-thickness medial meniscal tears were likely to be bucket-type tears regardless of the chronicity of the injury. Similarly, full-thickness lateral meniscal tears were more often flap-type tears independent of the time interval between injury and surgery. Partial-thickness tears were common both medially and laterally.Conclusions Patient's age and chronicity of ACL tear greater than 8 weeks are both significant factors in medial compartment chondral pathology. Patients with delayed reconstruction may have greater associated pathology.
Keywords: ACL; meniscus; cartilage; ACL deficiency